Business law today standard edition : text & summarized cases, legal, ethical, regulatory, and international environment - Miller, Roger LeRoy (WestLegal Studies in Business, 2000)
A credible law text with high interest and features exceptional visual appeal. This is a book that professors like, while students appreciate its thorough, dynamic coverage of traditional business law topics and exploration of summarized cases. This text explicitly meets the AACSB curriculum requirements.